359 The Cost of Illness of an Aneurysm Rupture: A Prospective Study to Quantity the Unseen Cost of Aneurysmal Subarachnoid Hemorrhage. (1st April 2022) - Mohammadi, Nicki; Spica, Natalia R.; Yaeger, Kurt; Chada, Deeksha; Smith, Colton; Reynolds, Alexandra; Lay, Cappi C.; Mocco, J. D.; Dangayach, Neha; Kellner, Christopher P.
Abstract : INTRODUCTION: Subarachnoid hemorrhage (SAH) is a devastating neurological event affecting 1/10, 000 adults globally with a mortality of more than 30%. SAH is financially straining for both the patient and caretaker due to its high morbidity, prolonged hospital stay, intensive treatments, and involved recovery. In this prospective study, we aim to quantify the total direct and indirect costs of SAH throughout the acute and subacute care periods. METHODS: Patients and their self-reported primary caregivers were prospectively followed for up to a year after the ictus hemorrhagic event, and queried monthly about expenses related to the recovery process. Additional clinical and cost information was obtained from the hospital finance department and directly from patient/caregiver follow-up interviews. RESULTS: Thirty-three patients were enrolled in this prospective study including 28 females (85%) and 5 males (15%) with a median (quartile range) age of 58 (47-66). Thirty-nine designated caregivers were also enrolled. The median ICU and hospital length of stay were 14 (11-19) and 19 (15-23) days, respectively. The median total cost for these patients was 135, 568 (38, 082 - 644, 688) and the median direct cost was 73, 161 (55, 138 - 91, 596) with a median expected patient payment of 114, 453 (70, 772 -204, 855). The median percentage of direct costs attributed to the ICU was 40% (32-45). Patients with Medicare had smaller ranges of costs. Additionally indirect hospital costs reported were for travel related costs (hotels, ride shares, metro cards), toiletries, home modifications and medications ranging from 0 to 1000 a day. CONCLUSION: SAH is consistently a devastating neurological event affecting active members of society and their social networks. Its complicated course and recovery process can leave patients confined to a hospital for extended periods of time. As providers, we must investigate avenues to mitigate the costs and burdens patients and their support networks face.